PERPINDAHAN PANAS PADA PIPA HEAT EXCHANGER DENGAN PIPA BERBAHAN KACA, TEMBAGA, DAN TEMBAGA YANG DILAPIS RESIN - Nuramal, Agus; Puspawan, Angky; Pratama, Gilang Giyas (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2020)
In this study, a heat exchanger will be designed with the principle of tube-pond, normal water flowing tubes and hot water-filled ponds. This study aims to determine the heat transfer characteristics of glass pipe, copper, and resin coated copper.The materials used in the tube were glass, copper, and resin coated copper, polyester resin of yukalac BTQN 157 and a catalyst of methyl ethyl ketone peroxide. In the test, the water temperature variation in ponds was 70?C, 80?C, and 90?C. At each temperature, the test was carried out by flowing normal water into the tube by varying the discharge by 1lpm, 0.8lpm, 0.6lpm, 0.4lpm, and 0.2lpm. The values for the temperature in and out of the water in the tube are obtained. So that the overall heat transfer coefficient value and its effectiveness can be calculated.The results showed that the higher the discharge, the overall heat transfer coefficient on the tube increased. where the highest value is in the copper tube meterial at 1 lpm discharge, which is at 80?C pond temperature of 1544.163 W / m2?C. While the smallest value of the overall heat transfer coefficient is the glassmaterial at the time of discharge 0.2 lpm, which is at a temperature of 90?C of 199.5889 W / m2?C